Kinetic parameters as determinants of vertical jump performance. DOI: 10.5007/1980-0037.2012v14n1p41 - Saray Giovana dos Santos; Daniele Detanico; Juliano Dal pupo (Universidade Federal de Santa Catarina, 2012)
The aim of this study was to identify force and velocity parameters related to vertical jump performance in counter movement jump (CMJ) and squat jump (SJ), and to compare these parameters between sprint runners and volleyball players. Twenty-four male athletes (12 regional/national-level sprint runners and 12 national-level volleyball players) participated in this study. The athletes performed CMJ and SJ on a force platform. The following variables were analyzed: jump performance (jump height and power), peak velocity (PV), absolute and relative maximum force (Fmax), rate of force development (RFD,) and time to reach maximum force (TFmax). In CMJ, jump height was correlated with PV (r=0.97) and normalized Fmax (r=0.47), whereas jump power was significantly correlated with all variables, except for Fmax (r=0.12). In SJ, PV and normalized Fmax were significantly correlated with jump height (r=0.95 and r=0.51, respectively) and power (r=0.80 and r=0.87, respectively). In addition, TFmax was inversely correlated with power (r=-0.49). Runners presented higher performance variables (height and power), normalized Fmax and PV than volleyball players in both CMJ and SJ. In conclusion, velocity and maximum force were the main determinants of height and power in the two types of vertical jump. However, explosive force (RFD and TFmax) was also important for power production in vertical jumps. Finally, runners presented a better vertical jump performance than volleyball players.